ACINIC CELL CARCINOMA OF THE MINOR SALIVARY GLANDS: A CASE REPORT - O. A. Saprina; M. A. Kropotov; T. T. Kondratyeva (Опухоли головы и шеи)
Acinic cell carcinomas (ACC) constitute 5 to 11 % of all salivary gland cancers. ACCs arise from the reserve precursor cells of the terminal and intercalated ducts. The tumor results from the neoplastic proliferation and aberrant differentiation of reserve pluripotent cells that are normally located in the transition of acini into the intercalated ducts of the salivary gland and/or into the intercalated ducts proper of mature salivary glands. ACCs chiefly affect the major salivary glands; sporadic cases of its involvement of the minor salivary glands have been described in the literature. This paper presents a clinical case of ACC of the minor salivary glands.